Magnetic-lazer modulation of specific humoral immunity in pregnant women with anemia - S. Yu. Yuriyev (Bûlleten' Sibirskoj Mediciny, 2011)
This article presents the comparative analysis of humoral and cellular immunity indicators under the influence of magneticlaser effect in 2 frequency ranges (150—1 5000 Hz) for treatment of pregnant women with mild anemia against the background of chronic gastritis, associated with contamination gastrointestinal tract Helicobacter pylori. The application of magnetic-laser effect in frequency 150 Hz allows to raise of hemoglobin lowers the titre of antibodies to Helicobacter pylori. The moderate stimulation of Th1 link withoit activation of humoral immunity is optimal in treatment of benign anemia of pregnancy.